Low-altitude wind shear and its hazard to aviation : report of the Committee on Low-Altitude Wind Shear and Its Hazard to Aviation : a joint study (National Academy Press, 1983)
Congressional concern over the crash of Pan American World Airways Flight 759, a Boeing 727, minutes after takeoff from the New Orleans International Airport on July 9, 1982, resulted in legislation passed in December 1982 providing that the FAA enter into an agreement with NAS to study and assess the hazards of low-altitude wind shear on takeoff and landing aircraft operations. To accomplish this task the NRC established the Committee on Low-Altitude Wind Shear and Its Hazard to Aviation, consisting of two panels: the Panel on Low-Altitude Wind Variability and the Panel on Aircraft Performance and Operations. The committee's principal finding confirmed that low-altitude wind variability (or wind shear) presents an infrequent but highly significant hazard to aircraft landing or taking off. Fortunately, most severe types of wind shear are relatively infrequent, generally short lived, and affect only local areas. Some wind shears have been understood by meteorologists for a number of years. These include those found in gust fronts, warm and cold air-mass fronts, mountain waves, low-level jet streams, gravity waves, terrain-induced turbulence, and sea-breeze fronts. Most are predictable, sometimes hours in advance. The more-skilled pilots recognize the potential presence of these shears and the dangers they pose. Scientists have recently begun to recognize the importance of storm downdrafts that are unusually small in horizontal cross sections and that are of short duration. Such downdrafts have been called microbursts. These often severe but localized events present the greatest danger to aircraft operations. Wind shear that resulted from the strongest microbursts actually measured in the summer of 1982 Joint Airport Weather Studies (JAWS) in Denver could not have been penetrated safely if encountered below 300-500 feet of altitude by an aircraft during takeoff or landing.